2008
DOI: 10.1177/1933719108317299
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Brain Injury in Neonatal Hypoxic—Ischemic Rats by Intracerebroventricular Injection of Neural Stem/Progenitor Cells Together With Chondroitinase ABC

Abstract: Perinatal hypoxia-ischemia (HI) remains a critical issue. Cell transplantation therapy could be a potent treatment for many neurodegenerative diseases, but limited works on this kind of therapy have been reported for perinatal HI. In this study, the therapeutic effect of transplantation with neural stem/ progenitor cells (NSPCs) and chondrotinase ABC (ChABC) in a neonatal HI rat model is evaluated. Histological studies showed that the unaffected area of the brain in animals treated with NSPCs together with ChA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 46 publications
0
37
0
2
Order By: Relevance
“…Other studies have shown effects of ChABC on axonal conduction, synapse formation, cell adhesion, growth factor diffusion, neuronal nets, and inflammation (5,11,28,29). In contrast, one prior study found no effect of ChABC, given as a single intracerebroventricular injection 24 h after neonatal hypoxic-ischemic brain injury in rats, on the wet weight of surviving brain tissue (30).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other studies have shown effects of ChABC on axonal conduction, synapse formation, cell adhesion, growth factor diffusion, neuronal nets, and inflammation (5,11,28,29). In contrast, one prior study found no effect of ChABC, given as a single intracerebroventricular injection 24 h after neonatal hypoxic-ischemic brain injury in rats, on the wet weight of surviving brain tissue (30).…”
Section: Discussionmentioning
confidence: 92%
“…Whether the effects of ChABC or glypican and such antibodies are additive will be of interest to explore, as will the combined effects of ChABC or glypican and transplantation, which has proved more efficacious than either treatment alone in models of retinal degeneration (40), neonatal hypoxia-ischemia (30), and spinal cord injury (41).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, an improved motor function is observed in the treated animals (Daadi et al, 2010). It was also reported that NSPC can decrease HI brain injury, when injected in combination with chondroitinase ABC, an enzyme that degrades glycosaminoglycans side chains of chondroitin sulphate proteoglicans (Sato et al, 2008).…”
Section: Neural Stem/progenitor Cell Transplantation In Hiementioning
confidence: 87%
“…Referência Yasuhara et al 57 Sato et al 28 de Paula et al 38 Yasuhara et al 40 PimentelCoelho et al 37 Jenny et al 31 van Velthoven et al 56 Lee et al 55 ↓ dano cerebral (CTN+ChABC < CTN = VEH); ↑ peso cerebral (CTN+ChABC > CTN = VEH) (7 dias pT) Nenhum efeito sobre a atrofia cerebral 3 semanas pT ↑ níveis cerebrais de GDNF, BDNF e NGF 3 dias pT (CTCUH < CTCUH+M); ↑ densidade dendrítica na região hipocampal de CA1 14 dias pT ↓ morte neuronal e expressão de caspase 3 no estriado isquêmico 2 dias pT; ↓ ativação microglial no córtex 7 dias pT Formação de agrupamentos celulares com superexpressão de FGF-2 em áreas perivasculares T-P12: ↓ lesão cerebral (18 dias pT); ↑ neuro-e oligodendrogênese, e ↓ proliferação microglial no hipocampo e córtex isquêmico (7 e 18 dias pT); ↑ proliferação de astrócitos no hipocampo, e ↓ no córtex isquêmico (7 dias pT). T-P19: ↓ lesão cerebral (18 dias pT) Nenhum efeito sobre a atrofia cerebral 6 semanas pT…”
Section: Tabela 1 -Revisão Das Publicações Sobre Terapia Celular Em Hunclassified
“…Um exemplo disso é a utilização de condroitinase ABC (ChABC) associada ao transplante intracerebroventricular de CTN em ratos neonatos submetidos à HI que resultou na redução acentuada do dano cerebral 28 . Devido à capacidade de promover plasticidade cerebral, os autores sugerem que a ChABC teria facilitado a adesão e migração de CTN para áreas isquêmicas.…”
Section: Migração Celularunclassified